EASTERN AND WESTERN PHILOSOPHIES OF DIVINITY IN THE ANALYSIS OF LANGUAGE AND GENDER COSMOLOGY - fadlan (Mahiyah: Journal of Islamic Thought and Philosophy, 2025)
This article examines the issue of divinity from a philosophical perspective by comparing Eastern and Western thought, with a primary focus on analyzing how humans perceive God from these two viewpoints, rather than examining the nature of His transcendent and complex absoluteness. This study specifically limits its scope to two key objects: God in the context of language and God in the context of gender cosmology, with the aim of defining and distinguishing these two concepts, identifying the causes of their differences, and analyzing their influence or implications on life. Through the use of descriptive-analytical and heuristic methods, supported by structuralist approaches, historical analysis, and ideological critique, I found that Eastern conceptions of God tend to be anthropocentric and masculinist, strongly cohesive with patriarchal culture. Conversely, Western conceptions of God, particularly post-Enlightenment, have moved toward more objective and impersonal ideas, even reverting to the feminine attributes of nature—referred to by eco-feminists as “The Mother God”—as a form of resistance against authoritarian religious dogma. Overall, this study affirms that the conception of God is fundamental because human perspectives—whether of God as a cruel or loving entity—are directly reflected in and impact social reality and behavior.